2018
DOI: 10.1002/ejp.1335
|View full text |Cite
|
Sign up to set email alerts
|

The type of sport matters: Pain perception of endurance athletes versus strength athletes

Abstract: Background Studies assessing athletes’ pain sensitivity yield inconsistent data, which demonstrate either increased pain threshold and tolerance in athletes than controls or similar thresholds. This inconsistency may result from the variability in the type of sport practiced by the athletes and its effect on pain perception. For example, endurance athletes perform continuous intense exercise for prolonged durations, whereas strength athletes perform short bouts of extreme efforts. Consequently, endurance athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 61 publications
1
41
0
1
Order By: Relevance
“…The difference in training between the endurance athletes included in our study (cross country skiers and runners) and the soccer players were probably not enough to produce differences in pain thresholds. A recent study (Assa et al, 2019) that included more distinct types of sports, showed that athletes in strength sports, e.g., weightlifters, hammer-and shotput throwers had increased heat pain thresholds compared to endurance athletes and controls. Like the pain tolerance measure, FPQ had also a significant impact on pain thresholds together with training volume per week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in training between the endurance athletes included in our study (cross country skiers and runners) and the soccer players were probably not enough to produce differences in pain thresholds. A recent study (Assa et al, 2019) that included more distinct types of sports, showed that athletes in strength sports, e.g., weightlifters, hammer-and shotput throwers had increased heat pain thresholds compared to endurance athletes and controls. Like the pain tolerance measure, FPQ had also a significant impact on pain thresholds together with training volume per week.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary, the findings on pain threshold and pain sensitivity (pain intensity) are mixed with some studies showing reduced thresholds in athletes compared to non-athletes, whereas other studies find results in the opposite direction (Tesarz et al, 2012;McDougall et al, 2020). The type of sport is probably a relevant cause for the divergent findings, and one study have showed that different sports are associated with different tolerance, thresholds and sensitivity for pain (Assa et al, 2019), regardless of the type of noxious stimuli.…”
Section: Introductionmentioning
confidence: 93%
“…To our knowledge, there is no study reporting the effects of endurance exercise on thermal thresholds. One prior study has reported pain thresholds assessed in endurance athletes versus strength athletes versus controls 32 . Based on thermal threshold changes, the authors suggest that endurance-based exercise is associated with improved pain inhibition, and strength-based exercise with reduced pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on thermal threshold changes, the authors suggest that endurance-based exercise is associated with improved pain inhibition, and strength-based exercise with reduced pain sensitivity. In general, athletes have shown decreased ratings in temporal summation of pain (see above) 32 . In our study, we assessed the wind-up ratio as the mechanical correlate for temporal summation, and found no direct effects of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The pain tolerance of competitors seems to vary depending on the discipline [20]. For example, endurance-based sports are associated with improved pain inhibition and strength-based sports are associated with reduced pain sensitivity [21,22] Physical exercise results in changes in sensitivity to pain [23]. The eccentric stretching group showed a higher pressure pain threshold (PPT), determined using a pressure algometer, after exercise than the non-eccentric group [24].…”
Section: Introductionmentioning
confidence: 99%